2019
DOI: 10.3390/ijerph16214276
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation Characteristics of PM2.5 in the Beijing–Tianjin–Hebei Region, China, from 2013 to 2018

Abstract: Air pollution, including particulate matter (PM2.5) pollution, is extremely harmful to the environment as well as human health. The Beijing–Tianjin–Hebei (BTH) Region has experienced heavy PM2.5 pollution within China. In this study, a six-year time series (January 2013–December 2018) of PM2.5 mass concentration data from 102 air quality monitoring stations were studied to understand the spatio-temporal variation characteristics of the BTH region. The average annual PM2.5 mass concentration in the BTH region d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 50 publications
4
9
0
Order By: Relevance
“…The “high-high” clusters were in south, southwest, and some northwest areas, while the “low-low” clusters were in northeast, central, and north areas in 2018–2019. This distribution pattern was also similar with some findings in other researches [ 47 , 48 , 49 ]. However, in the results of 2019–2020, the “high-high” clusters were mainly located in central, east, and south areas.…”
Section: Resultssupporting
confidence: 92%
“…The “high-high” clusters were in south, southwest, and some northwest areas, while the “low-low” clusters were in northeast, central, and north areas in 2018–2019. This distribution pattern was also similar with some findings in other researches [ 47 , 48 , 49 ]. However, in the results of 2019–2020, the “high-high” clusters were mainly located in central, east, and south areas.…”
Section: Resultssupporting
confidence: 92%
“… 21 Specifically, in some high-polluted areas such as Beijing-Tianjin-Hebei region of 2013, the annual average concentrations of PM 2.5 had reached 98.9 μg/m 3 , and daily average concentrations had exceeded 300 μg/m 3 . 22 23 Furthermore, the magnitude of the effects for each 10 μg/m 3 increment in PM 2.5 was also similar compared with other studies. 5 7 24–26 For example, one study found that each 10 μg/m 3 in PM 2.5 was associated with increases of 0.45 and 0.07 mm Hg in SBP and DBP, respectively.…”
Section: Discussionsupporting
confidence: 80%
“… 43 and Wang et al. 44 who observed low levels of variability of annual from monitoring sites. Given the reasonably good performance of our prediction model, the annual level predicted and monitored are highly consistent, which leads to generated errors being small.…”
Section: Discussionmentioning
confidence: 96%